Exercise-Mediated Skeletal Muscle-Derived IL-6 Regulates Bone Metabolism: A New Perspective on Muscle–Bone Crosstalk - Chenyu Zhu; Xiaoqing Ding; Min Chen; Jie Feng; Jun Zou; Lingli Zhang (Biomolecules, 2025)
Skeletal muscles and bones maintain musculoskeletal system function through their collaborative interaction, whereby muscles regulate bone metabolism via mechanical coupling. An increasing number of studies have shown that various cytokines secreted by skeletal muscles during exercise closely regulate the balance of bone homeostasis. Interleukin-6 (IL-6), one of the first muscle-secreted factors to be discovered, not only plays an important role in regulating the function of the muscle itself but also regulates bone metabolic processes in a bidirectional manner through multiple complex signal transduction pathways, thereby affecting the balance between bone formation and bone resorption. The exact mechanism by which IL-6 regulates bone metabolism is not fully understood, and there are few summaries on how exercise affects bone metabolism through IL-6 from skeletal muscles. Accordingly, this study will take skeletal muscle-derived IL-6 as an entry point to explore how the cross-organ regulatory activities of the muscles targeting bones during exercise affect bone metabolic processes. This study also aims to improve the mechanism of muscle–bone crosstalk under the effect of exercise and provide a theoretical basis and clinical diagnosis and treatment ideas from multiple perspectives for exercise to improve bone health.